Analysis of Architectural Design in the Sarijadi Bandung Contemporary Market Building - Ciptamelia Dawati Salmannisa; Yohannes Kusliansjah; Rumiati Rosaline Tobing (International Journal of Architecture and Urbanism, 2022)
Economic activity in Indonesia is one of the driving forces for people's lives in general. A traditional market building is one of the places where economic activity occurs, making it important to pay attention to its quality in terms of architecture and building management. However, the existence of traditional markets in Indonesia is synonymous with unmanaged and uncomfortable conditions. It can be found in almost all existing traditional markets. As a result, the government moved to repair traditional markets. It is the same as the Bandung City government, which revitalized the Sarijadi Bandung Traditional Market into a contemporary-style market, which the Governor of West Java, Ridwan Kamil, then used as a model for markets in Bandung City. The purpose of this study is to investigate and determine what is meant by contemporary meaning in the Sarijadi Contemporary Market building. The goal of this study was to add literature, references, and insights about architectural design in a contemporary-style market building, specifically the Sarijadi Contemporary Market in Bandung.